Synthesis of Ni2+/Natural Zeolite by Electro-Ion Exchange - I F Nurcahyo; Fitria Rahmawati; Lisa Agustina Nurlaila; Yuniawan Hidayat; Eddy Heraldy; Khoirina Dwi Nugrahaningtyas; Taufiiq-Yap Yun Hin (ALCHEMY Jurnal Penelitian Kimia, 2026)
Electro-ion exchange was carried out to synthesize Ni2+/natural zeolite at room temperature using various concentrations of Ni(NO3)2 of 0.05, 0.1, 0.15, and 2.0 M, zeolite wetting times of 0 and 24 hours, electrolysis times of 1, 2, and 3 hours, and voltages of 7.5, 15, and 28.4 V. The amount of Ni2+ that can be impregnated in the zeolite was monitored with Atomic Absorption Spectroscopy (AAS). The Ni2+/zeolite formed was characterized for its total acidity. The optimum conditions for this process are 28.4 V, 3 hours, and 0.1 M Ni(NO3)2. Under these optimum conditions, the Ni2+ content of the natural zeolite was 0.04 mmol/g, with a total acidity of 2.5 mmol/g. The increasing trend in the amount of Ni2+ content matched the trend in the total acidity. The synthesized Ni²⁺/natural zeolite is expected to be applied as a catalyst in reactions such as hydrogenation and hydrocracking.